ANALYSIS OF MENTAL HEALTH OF INMATES IN CLASS 1 PRISON CIREBON FACTORS AND MANAGEMENT STRATEGIES - Alfian, Hadi; Aprilllah, Yara Noerheti; Nurjanah, Najwa; Krisna R, Bayu; Nuranggita, Gina; Dikrurahman, Diky (Jurnal Abdisci, 2025)
Abstract: Background. The health of prisoners and inmates is one of the basic rights that must be guaranteed; those who serve sentences still have human rights. The state and relevant institutions should be accountable to prisoners, and prisoners should be able to obtain adequate health services. Aims. The purpose of this study is to analyze the factors that affect the mental health of prisoners in the Cirebon Class 1 Prison and the recovery strategies applied. Methods. Using qualitative methods, this study included interviews with nursing staff from the Rutan Clinic and an analysis of related documents. Result. The results of the study showed that the mental illness experienced by prisoners was mostly present before entering the detention camp. Of the 554 detainees and detainees, four of them suffered from mental disorders: bipolar, schizophrenia, and severe insomnia. There are no cases of mental health problems caused by illnesses in the detention center. The recovery strategy at the Cirebon Class 1 Detention Center prioritizes non-medical approaches such as mental guidance, religious activities (reading), social therapy, education and social activities (foreign language learning, scouting, art). This approach aims to avoid dependence on medications such as antidepressants that other prisoners may abuse. Regular surveillance is carried out to ensure positive development without drug addiction. However, the main challenge is that there is no professional or psychological consultation services available in this prison. Conclusion. This study highlights the importance of special attention to mental health in Cirebon Class 1 Prison as part of rehabilitation efforts. The non-medical approach used in the Class 1 Cirebon concentration camp will be a model for other detention centers. Implementation. However, more comprehensive treatment requires improvements in mental health facilities, such as the provision of specialized psychologists. The right strategy allows the prisoner to not only recover mentally but also make a positive contribution during detention.